Comparison of NOx emissions decreasing methods for biofuel boilers - Sereika, Titas; Buinevičius, Kęstutis; Jančauskas, Adolfas (International Conference “Environmental Engineering”, 2017)
The main idea of research is to figure out the emissions of nitrogen oxides reduction using various type of reduction methods. In experiments were used NOx reduction methods: high CO emissions generation, flue gas recirculation, water and water vapor supply, selective noncatalytic reduction (SNCR), and SNCR with flammable additive. This study presents e mission and combustion results obtained burning furniture production waste which generates higher rate of NOx emissions. The result of research shows, that CO emission has the biggest impact factor on reducing NOx emission. Burning fuel in combustion zone with first and secondary air ratio (40/60) and using methods for higher generation CO emissions reached 3.000 mg/m3 which reduces NOx emissions up to 83%. Using selective noncatalytic reduction with traditional and flammable additives reduction of NOx emissions reached up to 55%.